Pelatihan Analisis Data Penelitian Tindakan Kelas Bagi Guru SMA/SMK Di Wilayah Kabupaten Dan Kota Jayapura - Meinarni Asnawi; Pascalina Van Sweet Sesa (The Community Engagement Journal, 2021)
Several previous studies provide evidence that Classroom Action Research benefits teachers in improving a deep understanding of students’ thinking and learning, making changes to the teaching and developing teacher’s professional process, improving self-confidence in teaching ability and changing insights about teaching and learning and renewing commitment to the teaching profession. Currently the problem that occurs is that some teachers have not been optimal in conducting and producing good class action research reports, as well as creating articles sourced from class action research activities carried out that can then be published through scientific journals. In order to improve the competence of teachers to be able to produce a scientific paper that can be used as publication article of scientific journals carrying out class action research training activities for high school/vocational teachers in the Jayapura Regency and Jayapura City. Trainig Data Analysis Class Action Research uses the practical method of data analysis using SPSS analysis tools, the purpose of using this method is to ensure that this training can provide increased competence and understanding for participants during the training.